Post-Irradiated Human Submandibular Glands Display High Collagen Deposition, Disorganized Cell Junctions, and an Increased Number of Adipocytes. (June 2016) - Nam, Kihoon; Maruyama, Christina L.; Trump, Bryan G.; Buchmann, Luke; Hunt, Jason P.; Monroe, Marcus M.; Baker, Olga J.
Salivary glands are vital for maintaining oral health. Head and neck radiation therapy is one of the most common causes of salivary gland hypofunction. Little is known about the structural changes that occur in salivary glands after radiation therapy. The aim of this study is to understand the structural changes that occur in post-irradiated human (submandibular gland [SMG]) as compared with untreated ones. We determined changes in epithelial polarity, presence of collagen deposition, and alteration in adipose tissue. We used formalin-fixed paraffin-embedded human SMG from two female subjects exposed to head and neck irradiation. We utilized hematoxylin and eosin staining and Masson's Trichrome staining. The immunostained tissue sections were examined using confocal microscopy. The number and size of adipocytes per tissue section were calculated using ImageJ, Prism, and SPSS software. Post-irradiated human SMG displayed high collagen deposition, disorganized cell junctions, and an increased number of adipocytes as compared with non-irradiated controls. These findings are important to improve our understanding of the individual risk and variation in radiation-related salivary gland dysfunction.